Feminism, CSR and Global Governance: The Case of WEP - Cervi, Lucia (2012)
This study aims at understanding whether corporations can be considered facilitators of feminism through their involvement in international political and feminist projects. Such question stems from the acknowledgment of the new political role corporations are taking in global governance dynamics and institutions, which in turn allows them to be influential actors when it comes to tackling global political issues – such as, in this case, gender issues. In 2011 the UN Millennium Development Goals Report acknowledged gender issues and women’s rights as being one of the most urgent matters to be faced in the near future (UNMDG, 2011). Feminism itself has undergone a path defined by important achievements for women, such as equal political, civil and social rights. The focus of the feminist agenda has now been shifting towards economic equality, which goes beyond the concept of equal pay and embraces the idea of female empowerment in the business arena. In order to understand if and how corporations can foster the achievement of the feminist agenda, the case study of the United Nations Global Compact initiative Women’s Empowerment Principles (WEP) has been analyzed through the gathering of both primary and secondary data. The information gathered show how the relationship between business and institutions active in mechanisms of global governance is indeed intricate. Not only do the actors involved in the initiative prove to be very isolated from each other, but the corporations themselves understand and tackle gender issues in a plethora of different ways, therefore making the feminist agenda an ever important yet distant goal to achieve.